Methods for Quantifying Optic Disc Volume and Peripapillary Deflection Volume Using Radial Optical Coherence Tomography Scans and Association With Intracranial Pressure - Patel, Megh Dipak; Malhotra, Kiran; Shirazi, Zainab; Moss, Heather E. (Frontiers in Neurology, 2019)
Purpose: Papilledema and peripapillary deformation of Bruch’s membrane(BM) are associated with elevated intracranial pressure(ICP). We have developed a novel methodology to measure these parameters using a radial optical coherence tomography(OCT) scan pattern and apply this to test the hypothesis that ICP is associated with volumetric features of ophthalmic structures. Methods: 6-radial OCT B-scans centered over the optic nerve head were acquired in 17 subjects(30 eyes) before lumbar puncture with measurement of ICP(range:10-55 cm H2O). Internal limiting membrane(ILM) and BM were segmented. Three definitions of BM were studied to account for imaging artifact affecting peripapillary BM: connecting rater-identified BM margins(traditional), connecting rater-identified BM 1.6mm on either side of the ONH(estimated), and excluding BM in the central 3.2mm of the images(excluded). Optic nerve head volume(ONHV), BM displacement volume(BMDV) and cup volume(CV) were calculated by interpolating between B-scans. Ganglion cell complex volume(GCCV) was measured in the macula. Linear generalized estimating equations(GEE) modeled ONVH, BMDV and CV as a function of ICP and GCCV. Results: Increased ONHV was associated with elevated ICP for traditional(p=0.006), estimated(p=0.003) and excluded(p=0.05) BM definitions. Decreased BMDV was associated with elevated ICP for traditional(p<0.0005), estimated(p<0.0005) and excluded(p=0.001) definitions. Decreased ONHV was independently associated with decreased GCCV(p=0.001) and decreased ICP(p=0.031) in multivariable models. CV was neither associated with ICP nor GCCV in univariate or multivariable models. Conclusions: Elevated ICP is associated with ONHV increase and BMDV decrease, calculated from OCT images accounting for image artifact. Ganglion cell atrophy affects the relationship between ICP and ONHV. OCT derived volumetric measures of the posterior eye may have application as biomarkers for elevated ICP.